The Influence of Third-Party Funds, Return on Assets, and Financing to Deposit Ratio on Sharia Banking Financing in MSMEs - -, Rahmanisa Aulia Safitri; Saparuddin Mukhtar; Siti Fatimah Zahra (Universitas Muhammadiyah Surabaya, 2024)
This article analyzes the determinants of MSME financing at Islamic Commercial Banks. This is measured by internal bank factors, namely Third-Party Funds, Return on Assets, and Financing to Deposit Ratio. This paper used time series data sourced from Otoritas Jasa Keuangan for the period January 2021 - December 2023. Through multiple linear regression analysis with the Ordinary Least Square (OLS) method, it can be concluded that: First, partially, TPF and FDR have a significant positive effect on MSME Financing, while the ROA has nonsignificant negative effect on MSME Financing for Islamic Commercial Banks. Second, simultaneously, all variables have a significant positive effect on MSME Financing for Islamic Commercial Banks. With these results, it is hoped that this research can contribute to policy or decision making for Islamic Commercial Banks to improve financing distribution to the MSME sector, both working capital financing and investment financing for the MSME sector in Indonesia.